Limitations and uses of gastrojejunal feeding tubes. Issue 2 (1st February 2002) - Godbole, P; Margabanthu, G; Crabbe, D C; Thomas, A; Puntis, J W L; Abel, G; Arthur, R J; Stringer, M D
Abstract : Background: Gastrostomy feeding is a well established alternative method to long term nasogastric tube feeding. Many such patients have gastro-oesophageal reflux (GOR) and require a fundoplication. A transgastric jejunal tube is an alternative when antireflux surgery fails, or is hazardous or inappropriate. Aims: To review experience of gastrojejunal (G-J) feeding over six years in two regional centres in the UK. Methods: Retrospective review of all children who underwent insertion of a G-J feeding tube. Results: There were 18 children, 12 of whom were neurologically impaired. G-J tubes were inserted at a median age of 3.1 years (range 0.6–14.7) because of persistent symptoms after Nissen fundoplication (n = 8) or symptomatic GOR where fundoplication was inappropriate. Four underwent primary endoscopic insertion of the G-J tube; the remainder had the tube inserted via a previous gastrostomy track. Seventeen showed good weight gain. There was one insertion related complication. During a median follow up of 10 months (range 1–60), four experienced recurrent aspiration, bilious aspirates, and/or diarrhoea. There were 65 tube related complications in 14 patients, necessitating change of the tube at a median of 74 days. Jejunal tube migration was the commonest problem. Five died from complications of their underlying disease. Conclusions: Although G-J feeding tubes were inserted safely and improved nutritional status, their use was associated with a high rate of morbidity. Surgical alternatives such as an Roux-en-Y jejunostomy may be preferable.